Assessment of the effects of non-structural components on the seismic reliability of structures via a block diagram method. (January 2023) - Mohsenian, Vahid; Gharaei-Moghaddam, Nima; Mariani, Stefano; Hajirasouliha, Iman
Abstract: Under a specific ground motion excitation, even if structural components all satisfy a target performance level, the serviceability of the structure might get affected by the performance of non-structural components. Although the overall performance of a structure is affected by the performance of both structural and non-structural components, seismic reliability and fragility analyses usually only focus on the structural elements and their load-carrying capacity. The present study aims to assess the influence of the acceleration-sensitive non-structural components on the seismic reliability of the entire structure. The distinguishing feature of the proposed approach is the adoption of reliability block diagrams for the analysis of each structure, allowing for different combinations of damage for structural and non-structural components. Results are shown for 5-, 10- and 15-story buildings, to demonstrate the significant effects of non-structural components on their overall seismic reliability. Such effects prove to be more evident for the lower damage levels, and the higher seismic intensities. It is shown that non-structural components can lead to a reduction of the overall seismic reliability ranging from 22% to 100%, for situations related to the life safety and collapse prevention performance levels, under the effects of the design basis and maximum considered earthquakes, respectively.